Comoros : Staff Report for the 2002 Article IV Consultation and Review of Performance Under a Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2004)
Political instability and weak macroeconomic management have generated negative real per capita gross domestic product growth rates, contributing to widespread poverty and a worsening of social indicators. The challenge is to attain a higher rate of growth on a sustained basis and raise the living standards of the Comorian population. Measures to improve revenue mobilization and reduce nonpriority expenditures are required. Executive Directors commend the steps taken by the authorities to improve the prudential regulations and internal controls of the central bank of Comoros.